(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The paper analyzes some of the issues related to surrogacy procedures carried out abroad, with reference to the recognition of foreign orders recognizing the parentage of the intended parent where surrogacy is prohibited. It will be seen how the obligation to recognize the status filiationis of the foreign-acquired child with respect to both the biological parent and the intended parent is also derived from EU law, to the extent that such disallowance results in the loss of status and restricts his or her freedom of movement and the expression of family ties within the territory of the EU. Lastly, the paper deals with the European Commission’s proposal December 7, 2022, for a Regulation on jurisdiction, applicable law, recognition of decisions and acceptance of authentic instruments in matters of parenthood and on the creation of a European Certificate of Parenthood.